2021
DOI: 10.3390/ijerph182312696
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Statistical Methods for Twin Studies Relating Exposure to Early Life Health Conditions

Abstract: When investigating disease etiology, twin data provide a unique opportunity to control for confounding and disentangling the role of the human genome and exposome. However, using appropriate statistical methods is fundamental for exploiting such potential. We aimed to critically review the statistical approaches used in twin studies relating exposure to early life health conditions. We searched PubMed, Scopus, Web of Science, and Embase (2011–2021). We identified 32 studies and nine classes of methods. Five we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Another strength is to have considered both singleton and twin data, using traditional and modern approaches at the same time. Indeed, whereas singleton studies are suitable for studying the effects of individual environmental exposures (using conventional regression approaches) or individual genes (using GWAS) on developmental outcomes separately, twin studies allow studying the relative contributions of the whole genome and exposome (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strength is to have considered both singleton and twin data, using traditional and modern approaches at the same time. Indeed, whereas singleton studies are suitable for studying the effects of individual environmental exposures (using conventional regression approaches) or individual genes (using GWAS) on developmental outcomes separately, twin studies allow studying the relative contributions of the whole genome and exposome (7).…”
Section: Discussionmentioning
confidence: 99%
“…Twins share several genes, as well as the prenatal and postnatal environment, and provide a unique opportunity to disentangle the relative contributions of the genome and the exposome (i.e., the totality of the exposures experienced by an individual throughout life) (6) in explaining inter-individual differences in developmental outcomes (7). Indeed, previous studies have reported considerable geographical differences in the relative contribution of environmental factors, mainly due to marked geographical differences in the inter-individual variation of maternal dietary habits and other family factors (8).…”
Section: Introductionmentioning
confidence: 99%
“…These variables include additive genetic (A), common (or shared) environmental (C) and unshared (or unique) environmental (E) components. The random variables are expected to be mutually independent within a single twin and to follow a conventional normal distribution within the same twin [ 24 ]. For the ACE analysis, version 2.19.5 of the OpenMx package for structural equations and other statistical modeling has been used under version 3.6.3 of the R programming language [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, the "Health and Environment-wide Associations based on Large population Surveys" (HEALS) project (FP7-ENV-2013-603946 http://www.heals-eu. eu/) was funded by the European Commission with the aim to describe in a series of about 335,000 individuals the internal exposome by integrating omics and biomonitoring data through population studies taking into account different levels of environmental exposure, age-specific windows of exposure, and genetic variability (17)(18)(19). Notably, the HELIX project (https://www.…”
Section: The Exposome: An Innovative Approach For Assessing Environme...mentioning
confidence: 99%